The Role of Zakat and Wakaf in Reducing Economic Risks in Jayapura - Imran, Juani; Nur Laily M, Izzatul; Karman, Abdul (Filantropi : Jurnal Manajemen Zakat dan Wakaf, 2025)
Zakat and waqf are significant social financial instruments in Islam that play a vital role in reducing economic risks and improving the welfare of society. Zakat, as an obligatory act for financially able Muslims, serves to redistribute wealth equitably and help those in need. Meanwhile, waqf involves giving assets for the public good in the long term, contributing to the development of education, health, and infrastructure. This study aims to see how zakat and waqf play a role in reducing economic risks, especially in the Jayapura area. In Indonesia, especially in Jayapura, the potential of zakat and waqf is very large in supporting economic growth and poverty alleviation. However, challenges such as public distrust of management institutions, low awareness of zakat obligations, and less than optimal utilization of waqf assets hinder its effectiveness. A SWOT analysis shows that with the right strategy, weaknesses and threats in zakat and waqf management can be overcome, maximizing their potential to improve community welfare. Collaborative efforts between the government, zakat and waqf management institutions, and the community are essential to improve literacy, transparency, and accountability in managing resources so as to optimize the role in reducing economic risks and promoting community welfare in Jayapura.